Manajemen Pemeriksaan Pajak Badan Secara Daring Pada Kantor Pelayanan Pajak Pratama Jakarta Pulogadung - Cynthia Febriyani; Irawati Irawati (Jurnal Ilmu Administrasi Publik, 2022)
The purpose of this study is to analyse the management of online corporate tax audits at the Pulogadung Small Taxpayers Office, to analyse the role of the tax authorities in the implementation of online corporate tax audit management at the Pulogadung Small Taxpayers Office, and to analyse the efforts put forth by the Pulogadung Small Taxpayers Office to overcome existing challenges. This study employs qualitative approaches with the use of observation, interviews, and documentation studies. The author concludes that the tax audit is still not excellent. The Covid-19 epidemic presented little challenges for the tax examiner, which resulted in minor communication disruption. Efforts are being made to overcome challenges in online tax audit management at Jakarta Pulogadung Small Taxpayers Office by employing internal communication between taxpayers' taxes and tax audits to the greatest extent feasible, using social media to prevent misunderstandings. Recommendations for Jakarta Pulogadung Small Taxpayers Office to improve the effectiveness of online inspections by installing WiFi networks at various locations.